Greetings in Italian and German. Corpus-based Reflections in the Margins of FRAME - Gensini, Sabine E. Koesters; Schafroth, Elmar (ANNALI. SEZIONE GERMANICA. Rivista del Dipartimento di Studi Letterari, Linguistici e Comparati dell’Università degli studi di Napoli L’Orientale, 2021)
Based on the experience with the research project FRAME (Fraseologia multilingue elettronica, i.e. Electronic Multilingual Phraseology), this article will show to what extent formulae (here: salutations) that seem pragmatically unproblematic at first glance are in reality not at all easy to grasp in lexicography and to convey in language teaching. For this purpose, an exact corpus-based analysis of the pragmatic restrictions of the forms within the respective individual language microsystem of the salutation formulae is indispensable. This allows to show the contexts of use of the selected salutations in Italian and German and to illustrate the lexicographical consequences for the creation of the respective dictionary articles in FRAME. The theoretical background of these considerations is determined by Construction Grammar and (phraseological) pragmatics, whereas the methodological approach is primarily based on corpus linguistics.